THE UTILIZATION OF INSTAGRAM MICRO-INFLUENCERS FOR WARDAH BRAND AWARENESS IN THE DIGITAL ERA - Rahmadanty, Salsabilla; Deni, Indira Fatra (Program Pascasarjana UIN Sumatera Utara, 2025)
In today's highly digital era, numerous business actors compete through social media platforms. The skincare industry, in particular, has emerged as one of the most dynamic sectors, experiencing rapid growth in recent years. Wardah, as a leading local brand, must maintain its branding by enhancing brand awareness. With the rising beauty trends and increasing consumer awareness of high-quality local products, competition among various local cosmetic brands has intensified. This study aims to analyze and understand the utilization of Instagram micro-influencer accounts as a means to build Wardah's brand awareness in the digital era. A qualitative research method is employed to address research questions that require explanations or insights related to social phenomena and their contexts, particularly the use of influencers on Instagram. The study involves interviews with five participants who meet specific criteria, namely micro-influencers affiliated with the Wardah Youth Ambassador program, with follower counts ranging from 1,000 to 100,000. This research seeks to identify the effectiveness of leveraging Instagram micro-influencers in enhancing Wardah’s brand awareness in the digital age.